2019
DOI: 10.1101/687962
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

NEIL2 plays a critical role in limiting inflammation and preserving genomic integrity in H. pylori-infected gastric epithelial cells

Abstract: The accumulation of Helicobacter pylori infectioninduced oxidative DNA damage in gastric epithelial cells is a risk factor for developing gastric cancer (GC); however, the underlying mechanisms remain poorly understood. Here we report that the suppression of NEIL2, an oxidized base-specific mammalian DNA glycosylase, is one such mechanism via which H. pylori infection may fuel the accumulation of DNA damage during the initiation and progression of GC. Using a combination of cultured cell lines and primary cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 58 publications
(59 reference statements)
0
2
0
Order By: Relevance
“…As we have shown previously that NEIL2 prevents DNA damage accumulation following infection with H. pylori (35), we, therefore, examined the level of oxidized DNA bases in WT. vs…”
Section: Edms Depend On Neil2mentioning
confidence: 99%
See 1 more Smart Citation
“…As we have shown previously that NEIL2 prevents DNA damage accumulation following infection with H. pylori (35), we, therefore, examined the level of oxidized DNA bases in WT. vs…”
Section: Edms Depend On Neil2mentioning
confidence: 99%
“…NEIL2's decreased level or loss of its activity, to a less extent, NEIL1, is a risk factor for the progression of cancers such as lung cancer and squamous cell carcinoma in the oral cavity (30)(31)(32)(33), and poor survival in patients with estrogenreceptor-positive breast cancer (34). Recently, we have shown that Helicobacter pylori-infection suppresses DNA base-excision repair enzyme NEIL2 and accumulates DNA damage (35).…”
Section: Introductionmentioning
confidence: 99%